Public Attention Towards Sustainability in the EU: An Exploration of Google Trends Data - Beraldo, Davide; Svensson Hahr, Nora; Trans, Martin (AoIR Selected Papers of Internet Research, 2026)
This research explores public attention towards sustainability in the European Union (EU) using Google Trends data. By leveraging Google’s Trends API, the study assesses the evolution and composition of public interest in sustainability across EU member states. Sustainability is a multi-dimensional concept and its definition has evolved over time to encompass several environmental, social and economic factors. Public attention to sustainability has generally increased in Europe over the past three decades, as indicated by numerous studies analyzing trends in public engagement and media coverage. However, given the difficulty of measuring public attention towards a topic directly, most large-scale analyses of public attention to sustainability rely on media coverage as a proxy. Thus, we suggest using Google Trends data to analyze public attention towards sustainability. Considering the variability of definitions associated with the term, instead of applying existing assumptions on what sustainability means in a certain point in time and in space, we reconstruct what topics, as defined by Google knowledge definitions, received the most public attention, based on users’ search practices. The analysis reveals a steady increase in public engagement with sustainability issues since 2018, with notable regional disparities between Western and Eastern Europe. The research identifies the most common topics associated with sustainability, such as energy, sustainable development, and environmental issues, while also highlighting the growing influence of economic and corporate dimensions in public discourse. We conclude with covering the main limitations with the proposed methodology, and outlining the analytical directions for future research.